Terminal 7-methyl-guanosine cap structure on the normally uncapped 5' noncoding region of poliovirus mRNA inhibits its translation in mammalian cells. - Hambidge, S J (1991)
We have used an RNA transfection assay to study the translation of cellular and viral mRNAs with and without 5'-terminal m7GpppG cap structures in human tissue culture cells. HeLa cells were transfected with in vitro-transcribed hybrid RNA molecules containing the 5' noncoding regions of either luciferase or poliovirus linked to the coding region of the firefly luciferase gene. Transcripts containing a capped luciferase 5' noncoding region produced luciferase, while similar uncapped transcripts did not. In contrast, transcripts containing a capped 5' noncoding region of poliovirus accumulated 10-fold-lower levels of luciferase than similar transcripts without a terminal cap structure. Inhibition of poliovirus mRNA translation by a 5'-terminal cap structure was not observed in in vitro translation systems. This finding indicates that factors involved in cap-independent translation of poliovirus RNA are quantitatively or qualitatively different in human tissue culture cells and in in vitro translation systems. Furthermore, this study emphasizes the importance of studying translational control of mRNAs in intact cells.